SPLIT-SPLIT PLOT DESIGN (SSPD) - Rizki Fatriasi; Dewi Anggraini; Dewi Sri Susanti (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2013)
Split-Split Plot Design (SSPD) is an extension of the Split Plot Design (SPD) where in SSPD has an additional sub-subplot. SSPD requires the same principles with SPD so the placement of factor is set to be the main plot for a less important factor, the subplot for a more important factor, and the sub-subplot for the most important factor. The purpose of the research is to explain the properties of usage and estimate the parameters of SSPD’s model.